Temporal Trends in the Initiation of Dialysis Among Patients With Heart Failure With or Without Diabetes: A Nationwide Study From 2002 to 2016 - Pauline Knigge; Sørine Lundberg; Jarl E. Strange; Mariam E. Malik; Nina Nouhravesh; Andrea K. Wagner; Gunnar Gislason; Emil L. Fosbøl; Nicholas Carlson; Deewa Zahir; Charlotte Andersson; Jawad H. Butt; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The incidence and distribution of acute and chronic dialysis among patients with heart failure (HF), stratified by diabetes, remain uncertain. We hypothesized that with improved survival and rising comorbidities, the demand for dialysis would increase over time. Methods and Results Patients with incident HF, aged 18 to 100 years, between 2002 and 2016, were identified using Danish nationwide registers. Primary outcomes included acute and chronic dialysis initiation, HF‐related hospitalization, and all‐cause mortality. These outcomes were assessed in 2002 to 2006, 2007 to 2011, and 2012 to 2016, stratified by diabetes. We calculated incidence rates (IRs) per 1000 person‐years and hazard ratios (HR) using multivariable Cox regression. Of 115 533 patients with HF, 2734 patients received acute dialysis and 1193 patients received chronic dialysis. The IR was 8.0 per 1000 and 3.5 per 1000 person‐years for acute and chronic dialysis, respectively. Acute dialysis rates increased significantly among patients with diabetes over time, while no significant changes occurred in those without diabetes, chronic dialysis, HF‐related hospitalization, or overall mortality. Diabetes was associated with significantly higher HRs of acute and chronic dialysis, respectively, compared with patients without diabetes (HR, 2.07 [95% CI, 1.80–2.39] and 2.93 [95% CI, 2.40–3.58] in 2002 to 2006; HR, 2.45 [95% CI, 2.14–2.80] and 2.86 [95% CI, 2.32–3.52] in 2007 to 2011; and 2.69 [95% CI, 2.33–3.10] and 3.30 [95% CI, 2.69–4.06] in 2012 to 2016). Conclusions The IR of acute and chronic dialysis remained low compared with HF‐related hospitalizations and mortality. Acute dialysis rates increased significantly over time, contrasting no significant trends in other outcomes. Diabetes exhibited over 2‐fold increased rates of the outcomes. These findings emphasize the importance of continued monitoring and renal care in patients with HF, especially with diabetes, to optimize outcomes and prevent adverse events.